2017
DOI: 10.1007/s11356-017-8552-1
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons in the leaves of twelve plant species along an urbanization gradient in Shanghai, China

Abstract: Plants, particularly their leaves, play an important role in filtering both gas-phase and particle-phase polycyclic aromatic hydrocarbons (PAHs). However, many studies have focused on the accumulation and adsorption functions of plant leaves, possibly underestimating the effects that plants have on air quality. Therefore, eight tree species from different locations in Shanghai were selected to assess PAH filtering (via adsorption and capture) using washed and unwashed plant leaves. The differences in the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
1
4
0
1
Order By: Relevance
“…In urban soils in China [ 31 ], soils of the Yangtze River Delta [ 40 ] and soils of the Yinma River Basin [ 41 ], the content of Phe is not the highest, but it still ranks in the forefront. For PAHs in plants, the dorminance of Phe has also been found in other studies [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 80%
“…In urban soils in China [ 31 ], soils of the Yangtze River Delta [ 40 ] and soils of the Yinma River Basin [ 41 ], the content of Phe is not the highest, but it still ranks in the forefront. For PAHs in plants, the dorminance of Phe has also been found in other studies [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 80%
“…The influencing factors in retaining PAHs depend on leaf morphology (species, leaf, branch) and the abundance of stomata, trichomes, and cuticular wax. Studies showed that the coated wax on leaf surfaces and stomata aids plants in battling dust and airborne elements attached to or trapped in (Muhammad Waqar Ashraf & Salam, 2012;Liang et al, 2017). Although PAHs accumulate mainly on the products surface, due to their lipophilic nature, some diffusion can occur to inner layers (Alagić et al, 2015), where water activity and fat content have a determinant role in migration rate (Gomes et al, 2013).…”
Section: Fate On Plant/food/humanmentioning
confidence: 99%
“…However, few studies have reported the application of this technique to monitor the contamination of plants or trees [ 27 , 28 ]. Indeed, the evaluation of urban plants’ contamination by PAH is reported by more classical analytical approaches, such as solid–liquid extraction, mostly using chlorinated solvents [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%